Personalized assessment and management of women at risk for breast cancer in North America. (March 2015) - Pruthi, Sandhya; Heisey, Ruth; Bevers, Therese
Many women at increased risk for breast cancer would benefit from referral for genetic testing, enhanced screening, preventive therapy or risk-reducing surgery. We present a visual model and a step-wise approach to assist with a personalized risk stratification and management of these women. We present current recommendations with respect to lifestyle behaviors and mammographic screening, and we review the current evidence regarding enhanced screening and risk-reducing therapies. We discuss the usefulness of three risk-assessment tools in determining whether a woman qualifies for genetic testing, enhanced screening or preventive therapy and present four cases to demonstrate the usefulness of this approach in the clinical setting.